2015
DOI: 10.1080/00218839.2016.1184845
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Varroa destructor by pseudoscorpions in honey bee hives confirmed by PCR analysis

Abstract: The pseudoscorpions, Nesochernes gracilis and Chelifer cancroides, appear to have potential for control of varroa mites (Varroa destructor), but have not been observed to predate on varroa in honey bee hives. A molecular method was developed to determine, without the need for observation, whether a candidate predator was eating varroa in commercial hives. DNA extracted from pseudoscorpions, which had been observed to have fed on varroa, and DNA from those that had not come in contact with varroa were amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Mass-rearing methods for two pseudoscorpions (Nesochernes gracilis and Heterochernes novaezealandiae) were developed in New Zealand, and N. gracilis showed the most promising role for biological control of Varroa (Read et al 2014). Also, a molecular technique based on detection of Varroa DNA in extractions of pseudoscorpion DNA was developed to confirm the predation in commercial hives without the need for observation (van Toor et al 2015). Rangel and Ward (2018) evaluated the ability of the predatory mite Stratiolaelaps scimitus (Mesostigmata: Laelapidae) to control Varroa under laboratory and field conditions.…”
Section: Predatorsmentioning
confidence: 99%
“…Mass-rearing methods for two pseudoscorpions (Nesochernes gracilis and Heterochernes novaezealandiae) were developed in New Zealand, and N. gracilis showed the most promising role for biological control of Varroa (Read et al 2014). Also, a molecular technique based on detection of Varroa DNA in extractions of pseudoscorpion DNA was developed to confirm the predation in commercial hives without the need for observation (van Toor et al 2015). Rangel and Ward (2018) evaluated the ability of the predatory mite Stratiolaelaps scimitus (Mesostigmata: Laelapidae) to control Varroa under laboratory and field conditions.…”
Section: Predatorsmentioning
confidence: 99%
“…Especially the modulation of VdNav1 channels from V. destructor, an important pest of honeybee hives, may provide new insights on how C. cancroides efficiently control Varroa mites. C. cancroides has previously been considered to protect honey bees from mite infestations (van Toor et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…They also considered the use of pseudoscorpions as a potentially viable option because they have been observed to feed on Varroa within A. cerana colonies ( Donovan and Paul 2006 ) and can be massed reared ( Read et al 2014 ). It was shown in a laboratory study that a single pseudoscorpion fed on as many as 1–9 Varroa per day ( Fagan et al 2012 ) and that the predation of Varroa by pseudoscorpions found in honey bee colonies was confirmed by molecular analysis ( van Toor et al 2015 ). However, feelings towards using pseudoscorpions to control Varroa are mixed as Thapa et al (2013) observed pseudoscorpions prefer to feed on dead A. cerana larvae and adults rather than Varroa .…”
Section: Biological Controlmentioning
confidence: 99%